2022
DOI: 10.1049/pel2.12407
|View full text |Cite
|
Sign up to set email alerts
|

Overview of monitoring methods of press‐pack insulated gate bipolar transistor modules under different package failure modes

Abstract: Press-pack insulated gate bipolar transistor modules (PP-IGBTs) have been widely used in high-voltage and high-power-density applications, such as high-voltage direct-current (HVDC) converters, because of their advantages of low thermal resistance, double side cooling, and short-circuit failure mode. Package failure is one of the main reasons for IGBT module failure. Package condition monitoring is the key to realizing modules fault diagnosis, condition prediction, and intelligent operation and maintenance. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(96 reference statements)
0
0
0
Order By: Relevance
“…The IGBT module's versatility allows it to be used in a broad range of applications, not only in consumer products, such as home air conditioning and washing machines, but also in industrial fields, such as smart grid technology, aerospace, and ship drives, etc IGBT's working environment is mainly characterized by high voltage, large current, and high power density. Therefore, the reliability of its packaging is crucial for ensuring a stable system operation [2]. Research results have shown that the failure of most IGBT devices is due to local overheating caused by excessive energy, which in turn, leads to catastrophic failure of the device [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The IGBT module's versatility allows it to be used in a broad range of applications, not only in consumer products, such as home air conditioning and washing machines, but also in industrial fields, such as smart grid technology, aerospace, and ship drives, etc IGBT's working environment is mainly characterized by high voltage, large current, and high power density. Therefore, the reliability of its packaging is crucial for ensuring a stable system operation [2]. Research results have shown that the failure of most IGBT devices is due to local overheating caused by excessive energy, which in turn, leads to catastrophic failure of the device [3,4].…”
Section: Introductionmentioning
confidence: 99%